2006
DOI: 10.1086/502806
|View full text |Cite
|
Sign up to set email alerts
|

The Structures of Letters and Symbols throughout Human History Are Selected to Match Those Found in Objects in Natural Scenes

Abstract: Are there empirical regularities in the shapes of letters and other human visual signs, and if so, what are the selection pressures underlying these regularities? To examine this, we determined a wide variety of topologically distinct contour configurations and examined the relative frequency of these configuration types across writing systems, Chinese writing, and nonlinguistic symbols. Our first result is that these three classes of human visual sign possess a similar signature in their configuration distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
120
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(127 citation statements)
references
References 18 publications
5
120
0
2
Order By: Relevance
“…Many of our other human inventions have been designed-either explicitly or via cultural selection over time-so as to minimize their demands on the brain. For example, writing and other human visual signs appear to have been optimized by cultural selection for our visual systems (Changizi, 2006(Changizi, , 2009Changizi & Shimojo, 2005;Changizi, Zhang, Ye, & Shimojo, 2006). The definitions in the dictionary are not identical to the meanings of words we have in our heads, missing out, for example, on metaphorical associations that may be part of an individual's meaning of the word (see, e.g., Fillmore, 1975;Lakoff & Johnson, 1980, 2003, but it would be surprising if the large-scale organization of the dictionary was not driven in some large part by the organization of our mental lexicon.…”
Section: Resultsmentioning
confidence: 99%
“…Many of our other human inventions have been designed-either explicitly or via cultural selection over time-so as to minimize their demands on the brain. For example, writing and other human visual signs appear to have been optimized by cultural selection for our visual systems (Changizi, 2006(Changizi, , 2009Changizi & Shimojo, 2005;Changizi, Zhang, Ye, & Shimojo, 2006). The definitions in the dictionary are not identical to the meanings of words we have in our heads, missing out, for example, on metaphorical associations that may be part of an individual's meaning of the word (see, e.g., Fillmore, 1975;Lakoff & Johnson, 1980, 2003, but it would be surprising if the large-scale organization of the dictionary was not driven in some large part by the organization of our mental lexicon.…”
Section: Resultsmentioning
confidence: 99%
“…The fractal dimension is related to the amplitude spectrum and has been shown to be regular for many natural forms (e.g., 1 A similar notion has recently been proposed in relation to human writing systems and natural scenes (Changizi et al 2006). 2 Other studies have used spectra to classify natural scenes, e.g.…”
Section: Introductionmentioning
confidence: 97%
“…It has therefore been suggested that they co-opt or "recycle" evolutionarily older circuits with a related function (1), thus enriching (without necessarily replacing) their domain of use. For instance, learning to read recruits a left infero-temporal area originally engaged in object recognition, and even the seemingly arbitrary shapes of our letters may originate in a neural repertoire of junctions detectors useful for scene recognition and available to all primates (2). In the case of mathematics, although foundational intuitions such as number sense (3) and spatial maps (4) are present in many animal species and in humans prior to education, mathematical constructions vastly exceed these initial domains of inherited competence.…”
mentioning
confidence: 99%